2013
DOI: 10.1097/meg.0b013e32835cb5c0
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and predictors of no treatment in anti-hepatitis C virus-positive patients at tertiary liver centers in Greece

Abstract: A significant proportion (>40%) of anti-HCV-positive patients visiting Greek tertiary liver centers do not receive antiviral therapy. Most of them are lost during the initial evaluation process, whereas the majority (>80%) of eligible patients who complete the initial evaluation eventually start antiviral therapy. The probability of treatment seems to be significantly associated with the treating physician, the alanine transaminase levels, and whether liver biopsy or transient elastography was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…Interestingly, a recent report from a retrospective study conducted in Greece obtained similar data [11]. In our study, reasons treatment was not indicated included patient's age or mild disease stage.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, a recent report from a retrospective study conducted in Greece obtained similar data [11]. In our study, reasons treatment was not indicated included patient's age or mild disease stage.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, age <58 years at inclusion, job employment, absence of HCC, elevated ALT levels, and genotype 2 were independent predictors of antiviral treatment initiation. Patients' age, high ALT and HCV genotype 2 were in common with the results of the previous studies [Bini et al, ; Butt et al, ; Kanwal et al, ; Hansen et al, ; Kramer et al, ; Papadopoulos et al, ]. Past international guidelines recommended antiviral treatment in patients with persistent high level of ALT [Strader et al, ; Farrell, ], and they have been associated with good adherence compared with those with normal ALT levels.…”
Section: Discussionsupporting
confidence: 76%
“…A recent study, based on data from a Danish nationwide cohort [Hansen et al, ], showed that 21% of HCV‐infected individuals had received HCV treatment and the cumulative chance of treatment initiation over 5 years was 33.0%. In Greece, a study at tertiary liver centers showed that antiviral therapy was initiated in 55% of anti‐HCV positive patients [Papadopoulos et al, ]. To the best of our knowledge, this is the first prospective cohort study to investigate the rate of antiviral treatment initiation for HCV infection in East Asia where HBV is more prevalent than HCV.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty to make the most of interferons is illustrated by the low treatment uptake in many countries. [100][101][102] Therefore, while robust evidence supports the effectiveness in responders to interferon-based therapy, there is a huge unmet need for those who respond poorly or cannot tolerate this regimen.…”
Section: Future Perspectivesmentioning
confidence: 99%